SOLID LIPID NANOPARTICLES: A REVIEW ON DIFFERENT TECHNIQUES AND APPROACHES TO TREAT BREAST CANCER - GAJBHIYE, SHILPA A.; PATIL, MORESHWAR P. (International Journal of Applied Pharmaceutics, 2023)
Breast cancer, the most common malignancy among women, is also the second-leading cause of cancer deaths all over the world. As commonly used chemotherapy drugs, which are given systematically, causes toxicity not only to cancerous cells but also to proliferating normal cells. Similarly, drug resistance leads to drastic side effects and treatment failure. Thus arises the need for improving the therapeutic index of anticancer drugs. Owing to these failures, nanotechnology holds significant promises. Using keywords like multi-drug resistance, effective targeting, therapeutics, intracellular pathways, efficacy, and breast cancer, references were looked up from specialised databases including Elsevier, Pubmed, and Cambridge from the year 1994 to 2023. This review was supplemented by a few references from Springer Nature and pertinent data from an online source. Along with online articles from Medscape, StatPearls, and The Lancet Respiratory Medicine, it was excellent. Supported literature was used to overcome these challenges; therapeutic drugs are encapsulated in nanoparticles. Concurrently, solid lipid nanoparticles (SLN), with their few merits, like enhancing the therapeutic profile, overcoming multidrug resistance, providing a targeted approach, and serving as a controlled release, have gained the attention of researchers. SLNs confine significant promises, overcome these challenges, and help to possibly deliver the drug to a specific part of the body, particular organ, or tissue by an actively or passively targeted delivery system, which will be beneficial in the diagnosis and treatment of breast cancer. The objective of this article is to highlight the factors that influence the targeted drug delivery system and resultant bioavailability and also provide updates on recent research and various approaches used for breast drug delivery systems.